Peran Administrasi, Supervisi, dan Manajemen Pendidikan dalam Meningkatkan Kualitas Pembelajaran di SD IT Al-Azhar Galang - Tiara Paramita Br Purba; Sindy Adella; Zumiati Syarah; Mursal Aziz (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to explore the role of administration, supervision and educational management in improving the quality of learning at SD IT Al-Azhar Galang using descriptive qualitative methods. The research was conducted through observation, interviews and document analysis of administration, supervision and educational management practices at the school. The research results show that the role of these three aspects is very important in improving the quality of learning at SD IT Al-Azhar Galang. Effective administration helps organize learning resources and processes, supervision provides constructive feedback to teachers to improve their performance, while good educational management ensures alignment between school goals and daily learning practices. The implication of this research is the importance of the coordinated role of administration, supervision and educational management in achieving optimal learning goals.